The Study of Bankruptcy Opportunities of Listed Companies on The Stock Exchange of Thailand in The Industrials Group - Supapattarapohn, Benjawan; Sanitnai, Kamolwan; Subantao, Thiphpharat; Wongwun, Phatcharida; Bureekhan, Phennapha; Sakornphitak, Wachiraphon; Khlongkhlaew, Onruethai; Saetang, Athittayakon; Maenman, Nilawan (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
The objective of this study was to examine the accuracy of bankruptcy risk predictions using the Z-Score, Zmijewski, and Springate models to identify the most suitable model for listed companies in the Industrials group on the Stock Exchange of Thailand. The research uses data from the financial statements of companies with a fiscal year-end dates on December 31st, from the year 2020 to 2023. The dataset consists of 312 records from non-financially distressed companies and 288 records from financially distressed companies. The results of the study on forecasting bankruptcy risk for listed companies in the Industrials group on the Stock Exchange of Thailand, using the Diagnostic Test to compare the effectiveness of the Z-Score, Zmijewski, and Springate models, indicate that the Springate model demonstrates the highest accuracy in predicting financial failure. The model achieved a maximum accuracy rate of 67.00%, a sensitivity of 62.50%, a specificity of 81.25%, and a positive predictive value of 91.35%. Article history: Received 18 October 2024 Revised 15 June 2025 Accepted 26 June 2025 SIMILARITY INDEX = 3.21 %